Development of eco-friendly ZnO inks for paper-based printed electronics - Rubin, Sabrina Josephine (2018)
In this work, we report the development of printable semiconducting inks compatible with screen-printing and paper technology and functional at room temperature without the need of post-deposition treatments. The developed eco-friendly inks are based on a dispersion of zinc oxide nanoparticles on a cellulose matrix. Several cellulose derivatives were used to design and engineer such inks looking for the best formulation, printing conditions and compatibility with cellulose-based substrates. The approach described here represents an innovative and versatile generation of semiconducting inks composed of some of the cheapest, renewable and highly abundant materials we can find on Earth, such as cellulose, able to be implemented as channel in printed transistors on paper. By using a cellulose-based ion gel as gate dielectric the printed ZnO transistors exhibit an Ion=of f ratio ranging from 103 to 105, sat values close to 9 cm2 V 1 s1 and gm of around 0.4 mS.